THE STRATEGY OF INSTITUTIONALITY OF PANCASILA VALUES IN THE PERSPECTIVE OF THE CULTURE OF THE MINANGKABAU CULTURE - Yulika, Febri; Mulyadi; Haq, Chairul; Miswar, Vanesha (Academic Journal Research, 2025)
Objective: Pancasila is extracted from the cultural treasures of the Indonesian nation itself, from the results of long and continuous interactions with various elements of the Indonesian nation which are diverse and of various colors, with various accompanying situations. Method: The noble values of Pancasila are excavations and filters of customary elements that exist and are spread throughout the archipelago. That is why Pancasila is very suitable to be used as a guideline and way of life, a guide for the life of the Indonesian people, more than any other philosophy that has ever appeared, was born and tested in the history of the Indonesian nation. Result: Materially Pancasila has fundamental values which are the crystallization of various local wisdoms. This proves that the noble basic values of Pancasila, among others, can be extracted from the Minangkabau customary sayings, which are sources and treasure troves of pearls of wisdom that contain very deep meanings. Novelty: The philosophy contained in the expression of the Minangkabau customary saying and the values of Pancasila, at least the two go hand in hand and synergize with each other in providing a philosophical basis for the life of the Indonesian nation. Efforts and strategies for institutionalizing Pancasila values based on local wisdom values must always be carried out in parallel and synergistic ways.